The Influence of Gender Inclusivity on the Stock Prices of IPO Companies on the Main Acceleration Board 2024 - Putri Wulandari; Hardiansyah Hardiansyah (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2025)
This study examines the impact of gender inclusivity in the board of directors and commissioners on daily stock prices, considering moderating variables such as company size and age. Regression analysis was conducted using data from listed companies, evaluating the variables of the percentage of female board directors (X1), percentage of female board commissioners (X2), company size (Z1), and company age (Z2). The results indicate that interactions between the percentage of female board members and company size (X1Z1, X2Z1) have a significant impact on stock prices, with p-values below 0.05. However, interactions with company age do not show significance. These findings highlight that while gender inclusivity affects stock price movements, its influence is stronger when combined with company size variables. This emphasizes the importance of considering gender diversity in corporate strategies to enhance market performance.